GAMBARAN PENGETAHUAN IBU NIFAS TENTANG ADAPTASI PSIKOLOGIS PADA MASA NIFAS DI KLINIK PRATAMA AFIYAH PEKANBARU TAHUN 2019 - silvia nova nova; Silisdawati Zagoto (Jurnal Ilmu Kebidanan, 2020)
Combination pills are tablets that are considered to be a trustworthy method of contraception. Contraceptive pills in Indonesia while its user is as much asgk 17.24% in 2017, among the 17.24% of users of contraceptive pills there are some users who experience side effects such as vomiting nausea 2.7%, not menstruation as much as 0.2% weight gain As much as 1.6% and headaches as much as 5.8% according to Kemenkes year 2018 initial Survey conducted in Puskesmas Rejosari Kota Pekanbaru Year 2019 There are 4422 people who consume KB pills, preliminary Survey There are 6 mothers who consume KB pill combination Experienced side effects like increased weight and embossed its black spots on the face. The purpose of this study is to know the description of KB acceptor behaviour against combination pill side effects. Quantitative research type with deskritif design. The population of mothers who consume KB pills in 2018 is 4422 people. Sampling techniques using sampling quota, samples used 30 mothers in the work area Puskesmas Rejosari who consume KB pill combinations that experience side effects. The results of the study obtained the majority of respondents had a positive behavior of 21 70% in the working area of Rejosari Puskesmas. Suggestions for respondents expected this research could add insight into the behavior or actions of the mother to the side effects experienced adding to this insight can be done in a way often follow the counseling about the KB that is held healthcare personnel In the Puskesmas, read a book on how to cope with the pill side effects combination and can also find info on the problems of side effects through social media.